2015
DOI: 10.3109/17435390.2015.1107147
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity assessment and bioaccumulation in zebrafish embryos exposed to carbon nanotubes suspended in Pluronic® F-108

Abstract: Carbon nanotubes (CNTs) are often suspended in Pluronic® surfactants by sonication, which may confound toxicity studies because sonication of surfactants can create degradation products that are toxic to mammalian cells. Here, we present a toxicity assessment of Pluronic® F-108 with and without suspended CNTs using embryonic zebrafish as an in vivo model. Pluronic® sonolytic degradation products were toxic to zebrafish embryos just as they were to mammalian cells. When the toxic Pluronic® fragments were remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 40 publications
(72 reference statements)
0
29
0
Order By: Relevance
“…Pristine CNTs have been shown to have high biocompatibility, with single-walled (SW), multi-walled (MW) CNTs or carboxylated MW pristine CNTs having little effect on embryo viability and development, even at high concentrations (200 ug/mL) [ 137 ]. In another study SW CNTs functionalized by polyethylene glycol increased mortality, delayed hatching and decreased total larval length only at the highest concentration tested (1 ppm), but with no genotoxicity observed and no evidence of the nanotubes being taken up by tissues [ 138 ].…”
Section: Selected Nanotoxicology Studies In Zebrafishmentioning
confidence: 99%
“…Pristine CNTs have been shown to have high biocompatibility, with single-walled (SW), multi-walled (MW) CNTs or carboxylated MW pristine CNTs having little effect on embryo viability and development, even at high concentrations (200 ug/mL) [ 137 ]. In another study SW CNTs functionalized by polyethylene glycol increased mortality, delayed hatching and decreased total larval length only at the highest concentration tested (1 ppm), but with no genotoxicity observed and no evidence of the nanotubes being taken up by tissues [ 138 ].…”
Section: Selected Nanotoxicology Studies In Zebrafishmentioning
confidence: 99%
“…Zebrafish Danio rerio Hamilton 1822 is a small vertebrate (Pisces: Teleostei) model that requires less expensive husbandry and accommodation than do mammals, commonly used for toxicity evaluation. [19][20][21][22] We have previously observed that liposomes and siRNAlipoplexes composed of dioctadecyldimethylammonium bromide or chloride (DODAB/DODAC) : monoolein (MO) induce dissimilar in vitro responses. 16 Moreover, zebrafish biology has other advantageous characteristics: (i) females have the capability to lay around 200-300 eggs per day every 5-7 days; (ii) equals the longevity and generation time of mice (3-5 months); and (iii) transparent embryos develop promptly into larvae, ex-utero, within 120 hours postfertilization (hpf ) 17,18 allowing in vivo real-time imaging of ongoing processes and significant reduction of experiment duration.…”
Section: Introductionmentioning
confidence: 99%
“…This high reproductive ability and fertility along with simple maintenance procedures contributes to the positive attributes of zebrafish for use in nanotoxicological analysis. The toxicity of almost all types of nanoparticles including metal [106], metal oxide [107], carbon [108], polymer nanoparticles [109], nanocomposites [110], zero-dimensional [58], one-dimensional [111], two-dimensional [112] and three-dimensional nanoparticles [113] have been evaluated directly using zebrafish with promising results as shown in Table 1. Zebrafish are also used to evaluate the genotoxicity of nanoparticles, as it is easy to analyze the genome of zebrafish compared to larger animals [114].…”
Section: -Zebrafish For Nanotoxicity Evaluationmentioning
confidence: 99%